OPTIMASI FAKTOR PROSES PEMBUATAN KOMPOSIT SEMEN/PLASTIK/FOAM DENGAN METODE GRAY-ROBUST DESIGN - Muhamad Fajri (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Technology in the field of konstruki continues to grow every day. One of the technological developments in the field of construction is material innovation in the manufacture of light bricks. Light bricks are cement and sand, but today's light brick making uses increasingly complex mixed materials. The manufacture of light brick is also one of the material innovations that are trending because it can recycle unused materials again such as plastic waste, the rest of clothes that are no longer used, rice husks, and foam agents. Plastic fibers are commonly used as toy-making materials, which have the potential to be used as a plus material in light bricks. This study used foam agent, plastic, and cement materials. With gray-robust design. The purpose of this study is to know the optimum value in light bricks from water absorption testing, heat absorptio and compressive strength that have optimal values. The result of the pene.